DIELECTRIC CHARACTERISTICS OF ENGINE OILS FOR POWER UNITS, AS MEASURED BY A CAPACITIVE SENSOR - I. V. Baturlia; A. I. Kuzmich; V. V. Baranov; V. A. Petrovich; V. Y. Serenkov; S. A. Zawatski; N. K. Fomenko; N. S. Kavalchuk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of the study sample, depending characteristics of dielectric losses of motor oils with different degrees of aging are given. The technology of controlling the parameters of oil power plants described by means of monitoring systems installed on mobile objects is proposed.